2017
DOI: 10.1016/j.jconrel.2016.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal skin patch based on reduced graphene oxide: A new approach for photothermal triggered permeation of ondansetron across porcine skin

Abstract: The development of a skin-mounted patch capable of controlled transcutaneous delivery of therapeutics through thermal activation provides a unique solution for the controlled release of active principles over long-term periods. Here, we report on a flexible transdermal patch for photothermal triggered release of ondansetron (ODS), a commonly used drug for the treatment of chemotherapy-induced nausea and vomiting and used as model compound here. To achieve this, a dispersion of ODS-loaded reduced graphene oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 54 publications
0
40
1
Order By: Relevance
“…It is also in contrast to the recently reported photothermal release of ODS on photothermally activatable skin patches: 24 irradiation for 30 min resulted in a release of 15% ODS, while electrochemical release of ODS after 30 min was between 5 and 7%. However, while the photothermal approach resulted in a release maximum after 30 min irradiation, the release of ODS as shown here is constant over a long period of time.…”
Section: Electrochemical Triggered Release Of Odscontrasting
confidence: 99%
See 3 more Smart Citations
“…It is also in contrast to the recently reported photothermal release of ODS on photothermally activatable skin patches: 24 irradiation for 30 min resulted in a release of 15% ODS, while electrochemical release of ODS after 30 min was between 5 and 7%. However, while the photothermal approach resulted in a release maximum after 30 min irradiation, the release of ODS as shown here is constant over a long period of time.…”
Section: Electrochemical Triggered Release Of Odscontrasting
confidence: 99%
“…Such a flux is highly promising for follow up transdermal studies where ODS fluxes between 1 μg cm −2 h −1 and 4 μg cm −2 h −1 are reported. 24,25,34 Considering that the usual oral dose of ODS is between 16 and 32 mg a day and the oral bioavailability of ODS is 60%, for an effective ODS delivery system, about 10-20 mg a day should be delivered into the blood circulation, i.e. 2.5-5 mg every 6 h. 35 A K/Au-prGO/ODS electrode of 1 cm 2 delivers about 282 μg ODS in 6 h. An electrode of around 10 cm 2 in size is theoretically needed to deliver the daily amount required.…”
Section: Electrochemical Triggered Release Of Odsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced graphene oxide (rGO) nanosheets with restored sp 2 network have most lately shown to be ideally suited for drug-loading-and drug-release-based applications using electrical (1)(2)(3) as well as thermal induced triggers. (4)(5)(6)(7)(8)(9)(10) Although the majority of the aromatic scaffold of rGO is devoid of any functional groups, a few carboxylic acid and alcohol groups are present at the edges and other defect points. This limits the effective functionalization of the rGO through covalent transformations.…”
Section: Introductionmentioning
confidence: 99%